PENGARUH PROMOSI, ULASAN KONSUMEN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TOKOPEDIA YANG DI MODERASI OLEH ERA REVOLUSI INDUSTRI 4.0. (Studi Pada Kecamatan Pondok Gede,Kota Bekasi ) - Nieke Masruchiyah; Pudji Astuty; Saeful Ardi (Jurnal Manajemen FE-UB, 2023)
The independent variables in this study are promotions, consumer reviews, and prices. The dependent variable is the purchase decision and the moderating variable is the industrial revolution 4.0. This research was conducted from September 2021 to February 2022. It was carried out in the Pondok Gede sub-district. The population used is the Pondok Gede sub-district community who use Tokopedia and have made at least 2 transactions. Respondents and samples used amounted to 101 respondents. The method used in this study is a quantitative method with a Likert scale. The data used is primary data. Primary data was obtained by distributing questionnaires as the instrument. Against a sample of 101 respondents. The analysis used is multiple linear regression and Moderated Regression Analysis (MRA) processed with the help of SPSS version 26. The results of this study indicate that (1) the promotion variable has no significant effect on purchasing decisions. (2) The consumer review variable has a positive and significant effect on purchasing decisions, (3) The price variable has a positive and significant effect on purchasing decisions, (4) the promotion variable, consumer reviews and price together have a positive and significant effect of 65.2% on purchasing decisions, (5) the moderating industrial revolution variable that strengthens the influence of promotion on purchasing decisions, (6) the moderating industrial revolution variable that strengthens the influence of consumer reviews on purchasing decisions, (7) the moderating industrial revolution variable that strengthens the effect of price on purchasing decisions. Based on the results of this study, the researchers provide suggestions, namely that it is hoped that Tokopedia will be able to increase promotions, motivate consumers to provide reviews and provide more competitive prices than other marketplaces and maximize technology in the 4.0 industrial revolution era to attract consumer purchasing power and company goals, and get more consumers many more in the midst of increasingly fierce competition.   Keywords: Promotion, Consumer Reviews, Price, Purchase Decision, Industrial Revolution 4.0.